Delayed Cerebral Injury in Adults With Bacterial Meningitis: A Novel Complication of Adjunctive Steroids?*. Issue 8 (August 2018) - Gallegos, Cinthia; Tobolowsky, Farrell; Nigo, Masayuki; Hasbun, Rodrigo
Abstract : Objectives: To report the prevalence of delayed cerebral injury in adults with bacterial meningitis and explore its association with adjunctive steroids. Design: Retrospective analysis of adults with bacterial meningitis between 2005 and 2016. Setting: Ten hospitals in the Greater Houston area. Patients: Consecutive subjects with culture proven community-acquired bacterial meningitis. Intervention: Subjects were categorized as receiving or not adjunctive steroids within 4 hours. Measurements and Main Results: A total of 120 patients were identified who were admitted with community-acquired bacterial meningitis. Delayed cerebral injury was seen in five of 120 patients (4.1%); all five patients had fever and abnormal neurologic examinations. Adjunctive steroids within 4 hours were more likely given to those with delayed cerebral injury (5/5, 100% vs 43/115, 37.5%; p = 0.01). Of the patients who developed delayed cerebral injury, three had Streptococcus pneumoniae, one had methicillin-resistant Staphylococcus aureus, and one had Listeria monocytogenes isolated. We observed an adverse clinical outcome as defined by the Glasgow Outcome Scale in four of the five patients (80%). Conclusions: Delayed cerebral injury occurred in 4.1% of adults with bacterial meningitis, and it was associated with the use of adjunctive steroids. Future studies should explore the etiology and prevention of this devastating complication.